The uniqueness form of Kendi from the museum collection / Azra Nazirah Azhar, Arba’iyah Ab. Aziz and Mohamad Kamal Abd. Aziz - Azhar, Azra Nazirah; Ab. Aziz, Arba’iyah; Abd. Aziz, Mohamad Kamal (Faculty of Art and Design, 2023)
In Southeast Asia, the Kendi is regarded as a type of traditional pottery. It can also be found in other countries, such as Asia, and the Middle East, and some European nations. Despite this, its usage is strongly related to Southeast Asia's culture. According to the study, although Kendi is no longer used in society, it is still used for home decorating. Misunderstandings and confusion regarding its usage have been caused by the word Kendi. In addition, younger generations may not be familiar with the type of shape and use of Kendi due to various technological innovations, such as water filters. The research aims to classify and identify the various characteristics of Kendi. In order to collect in-depth information, qualitative research methods which include observation and interview, were used. As a result of this research, it has become clear that Kendi comes in many forms. The shape of the Kendi, which is not only focused on one shape such as the shape of the round body, makes it a unique artifact. This research helps the community understand the value of art and Kendi, and it is hoped that various parties can do further research on it. This is because the Kendi has a variety of unique shapes and looks to be studied. The museum can also use this discovery for future research and knowledge. It is intended that future academics examine the form of this Kendi in greater depth, not only on the motifs and forms but also on the art of carving and the manner of creating Kendi found in Malaysia in particular.